Numerical simulation on the flame propagation in duct-vented gas explosion: The effect of duct length on the secondary explosion - Siti Zubaidah, Sulaiman; Nurul Syazwana, Noor Azmi; Azizan, Ramli; Rafiziana, Md Kasmani; Siti Kholijah, Abdul Mudalip; Rohaida, Che Man; Shalyda, Md Shaarani; Zatul Iffah, Mohd Arshad (IOP Publishing, 2019)
Duct venting is the most recognized explosion protection technique used in the industry. However, the key problem with this technique is the appropriate design of the duct size for an effective release material to prevent the secondary explosion that can cause further damage to the plant. Factors such as duct length and diameter have a significant effect on the duct venting mechanism that contributes to the second explosion. Thus in this study, the duct-vented gas explosion was simulated with the aim to investigate the influence of duct length focusing on the flame and pressure characteristics. From the simulation analysis, it shows that vessel interconnected with the duct with 0.05 m diameter and 0.5 m length experience a flame severe problem behavior to produce the secondary explosion effect.